Gaia data release 1: pre-processing and source list creation - Fabricius, Claus; Bastian, Ulrich; Biermann, Michael; Löffler, Wolfgang; Brüsemeister, Thomas; Hauser, Marcus; Jordan, Stefan; Lenhardt, Helmut; Stampa, Ulrike; Altmann, Martin; Hofmann, Wilfried (Astronomy and astrophysics, 2016)
Context. The first data release from the Gaia mission contains accurate positions and magnitudes for more than a billion sources, and proper motions and parallaxes for the majority of the 2.5 million Hipparcos and Tycho-2 stars. Aims. We describe three essential elements of the initial data treatment leading to this catalogue: the image analysis, the construction of a source list, and the near real-time monitoring of the payload health. We also discuss some weak points that set limitations for the attainable precision at the present stage of the mission. Methods. Image parameters for point sources are derived from one-dimensional scans, using a maximum likelihood method, under the assumption of a line spread function constant in time, and a complete modelling of bias and background. These conditions are, however, not completely fulfilled. The Gaia source list is built starting from a large ground-based catalogue, but even so a significant number of new entries have been added, and a large number have been removed. The autonomous onboard star image detection will pick up many spurious images, especially around bright sources, and such unwanted detections must be identified. Another key step of the source list creation consists in arranging the more than 1010 individual detections in spatially isolated groups that can be analysed individually. Results. Complete software systems have been built for the Gaia initial data treatment, that manage approximately 50 million focal plane transits daily, giving transit times and fluxes for 500 million individual CCD images to the astrometric and photometric processing chains. The software also carries out a successful and detailed daily monitoring of Gaia health.
Gesehen am 12.05.2020